Throwness as Reliable Path to the Genuine Exsitence of Human Beings - Jiang, Chenglinkuan (Transactions on Social Science, Education and Humanities Research, 2024)
The philosophical movement of existentialism has been significantly influenced by the contributions of Martin Heidegger and Jean-Paul Sartre, who are considered to be pivotal figures in this field. Although they both address fundamental aspects of the human condition, their philosophical methodologies differ significantly. Examining these divergent viewpoints is essential for understanding the depth and intricacy of the existentialist perspective. This article employs a comparative methodology to analyse the perspectives of Heidegger and Sartre on the fundamental aspects of human existence. The discussion will focus on Heidegger’s notion of Dasein, which refers to the fundamental state of human existence. It will examine how his concepts of finitude and geworfenheit (thrownness) influence our comprehension of authenticity. The text will analyse Sartre’s fundamental principle, which states that existence comes before essence. The concept emphasises the significance of individuals assuming responsibility for their actions and recognises the potential risks associated with making decisions in an uncertain environment. An analysis of Heidegger and Sartre in connection with Albert Camus and Simone de Beauvoir may reveal further nuances of existentialism. Through analysing these inquiries and exploring the interplay between existentialist philosophy and modern existence, researchers can develop a more profound understanding of the fundamental nature of humanity in a world where freedom and responsibility are intertwined.